CBCT in Modern Dentistry: Transforming Diagnosis and Treatment Planning (Academia Journal of Medicine, 2024)
Cone-Beam Computed Tomography (CBCT) has revolutionized modern den tistry, offering high-resolution, three-dimensional imaging that enhances diag nostic accuracy and treatment planning. This advanced technology provides  invaluable insights into dental structures, root canals, bone anatomy, and pathol ogies, resulting in better patient outcomes. By minimizing exposure to radiation  compared to traditional CT scans and offering detailed visualization beyond con ventional 2D radiography, CBCT stands as a transformative tool in various dental  specialties. This paper explores CBCT’s impact on contemporary dental practices,  its advantages, limitations, and future potential in improving dental care. intervention in implantology, endodontics, orthodontics, and maxillofacial surgery.1
Keywords: CBCT; 3D imaging; Diagnosis